Study of pleural fluid cholesterol compared with Light’s criteria to differentiate exudative and transudative pleural effusion in patients admitted at Tishreen University Hospital - غصينة أنس; محمد الخير; فيصل رضوان (Latakia University Journal -Medical Sciences Series, 2024)
Background: Pleural effusion is a manifestation of several diseases, both pulmonary and extra pulmonary, and may be an exudate or a transudate. In recent years, pleural fluid cholesterol has been proposed for separation of exudates from transudates. Objective: To study levels of pleural fluid cholesterol compared with Light’s criteria to differentiate between exudates and transudates. Materials and Methods: This was a Cross-Sectional study, conducted in the Department of Respiratory Diseases at Tishreen University Hospital in Lattakia during the period September 2022 to September 2023, 84 patients were included by adhering strictly to certain inclusion and exclusion criteria. Pleural fluid and serum protein, lactate dehydrogenase (LDH) and cholesterol were studied. Results: According to Light’s criteria 68 (%81) patients had exudate pleural effusion and 16 (%19) had transudate effusion. Pleural fluid cholesterol ˃ 45 mg/dl was considered as exudative pleural fluid, 67 (%79.8) patients had exudate pleural effusion and 17 (%20.2) patients had transudate. We compared between transudates and exudates based on disease diagnosis and Light’s criteria plus pleural fluid cholesterol, we noted highly significant difference between them (p value = 0.0001). The cut-off value of pleural fluid cholesterol 48 mg/dl was determined with sensitivity of %97.1 and specificity of %100 and p value = 0.0001. Conclusion: Pleural fluid cholesterol is a simple, cost effective and useful parameter in differentiating pleural exudates from transudates, with the advantage of requiring only one laboratory determination and no simultaneous blood sample, as compared to the use of Light’s criteria, which require four parameters.